Treatment of First-Time Perianal Abscess in Childhood, Balance Recurrence and Fistula Formation Rate with Medical Intervention - Gong, Zhenhua; Han, Meilin; Wu, Yibo; Huang, Xiong; Xu, Wei-Jue; Lv, Zhibzo (European Journal of Pediatric Surgery, 2018)
Purpose Because of differences in therapy for first-time perianal abscess, a wide range of recurrences and/or development of fistula-in-ano (RF) rates have been reported. The indication for determining when surgical intervention is needed remains obscure and controversial. This retrospective study sought to compare outcomes of conservative treatment with those after incision and drainage (ID) to determine the optimal time for surgical intervention.Methods A total of 697 patients with first-time perianal abscess were included in this study. The median patient age at the time of onset was 129 days (range: 5–5,110 days). The median follow-up period was 395 days (range: 120–760 days).Results Of the 697 patients with first-time perianal abscess, 355 (50.9%) patients who received conservative treatment had 12.7% (45/355) RF rate, which is less than that of abscesses treated with ID (24.6%, 72/297; p < 0.001). The median course was 23 (2,466) days, which did not differ significantly from that of abscesses with ID (18 [3,510] days) (p = 0.609). Forty-six (6.6%) patients with abscesses that perforated spontaneously had 10.9% (5/46) RF rate, which was less than that of abscesses with ID (p = 0.019), and the median course was 9 (3,316) days, which was shorter than that of abscesses with ID (p = 0.04).Conclusion Conservative treatment is a safe and effective technique for most first-time perianal abscesses with less recurrence and a lower fistula formation rate. Incision must be performed when an abscess is likely to spread or shows no sign of spontaneous perforation.
Keywords: perianal abscess; fistula-in-ano; children; treatment